Unlike Kangaroo care, mechanically simulated Kangaroo care does not change heart rate variability in preterm neonates. (June 2018) - Kommers, Deedee; Joshi, Rohan; Pul, Carola van; Feijs, Loe; Oei, Guid; Oetomo, Sidarto Bambang; Andriessen, Peter
Abstract: Background: While numerous positive effects of Kangaroo care (KC) have been reported, the duration that parents can spend kangarooing is often limited. Aim: To investigate whether a mattress that aims to mimic breathing motion and the sounds of heartbeats (BabyBe GMBH, Stuttgart, Germany) can simulate aspects of KC in preterm infants as measured by features of heart rate variability (HRV). Methods: A within-subject study design was employed in which every routine KC session was followed by a BabyBe (BB) session, with a washout period of at least 2 h in between. Nurses annotated the start and end times of KC and BB sessions. Data from the pre-KC, KC, post-KC, pre-BB, BB and post-BB were retrieved from the patient monitor via a data warehouse. Five time-domain features of HRV were used to compare both types of intervention. Two of these features, the percentage of decelerations (pDec) and the standard deviation of decelerations (SDDec), were developed in a previous study to capture the contribution of transient heart rate decelerations to HRV, a measure of regulatory instability. Results: A total of 182 KC and 180 BabyBe sessions were analyzed in 20 preterm infants. Overall, HRV decreased during KC and after KC. Two of the five features showed a decrease during KC, and all features decreased in the post-KC period ( p ≤ 0.01). The BB mattress as employed in this study did not affect HRV. Conclusion: Unlike KC, a mattress that attempts to mimic breathing motion and heartbeat sounds does not affect HRV of preterm infants. Highlights: Features of heart rate variability were analyzed in preterm infants before, during and after Kangaroo care Features of heart rate variability were also analyzed before, during and after mechanical simulation of Kangaroo care Kangaroo care exerts an immediate stabilizing effect on autonomic regulation as seen by changes in heart rate variability This stabilizing effect was not mimicked by a mattress that simulates breathing motion and heartbeat sounds